Public knowledge and beliefs about the irritable bowel syndrome - results from the SOMA.SOC study - Olaf von dem Knesebeck; Bernd Löwe; Daniel Lüdecke; Johanna S. Bobardt; Rieke Barbek (BMC, 2024)
Abstract Background Despite the epidemiological and economic relevance of the irritable bowel syndrome (IBS), there is a lack of research on what the general public knows and thinks about this condition (IBS literacy). Therefore, the aim of this study was to explore public knowledge and beliefs about IBS in Germany. Moreover, associations of knowledge and beliefs about IBS with socio-demographic characteristics as well as illness and treatment experiences were analysed. Methods Analyses made use of a national telephone survey (N = 1,205). A carefully developed vignette describing a person with typical symptoms of IBS was presented. Respondents were then asked to name the disease in question and beliefs about causes and treatment options were assessed. For the analyses respondents were divided into three groups: (1) people who never had IBS symptoms, (2) people who had or have IBS symptoms but never were in treatment and (3) individuals who reported to be or have been treated for IBS symptoms. Results Less than 4% of the respondents recognized IBS after presentation of the vignette. About 75% positively evaluated treatability while psychotherapy was evaluated more effective than medication. Stress and unhealthy lifestyle were the most frequently endorsed possible causes of the presented IBS symptoms. There were variations in knowledge and beliefs about IBS according to age, gender, and education. We found minor differences in beliefs and knowledge between individuals who had or have symptoms but never were in treatment and those without respective illness experience. Respondents with illness/treatment experiences rated their knowledge significantly better than those without any experiences. Conclusions Results indicate low levels of public knowledge about IBS regarding illness recognition in Germany. A majority disagreed that they have good knowledge about IBS symptoms. Against this background, it seems reasonable to develop and test interventions to improve IBS literacy by increasing knowledge about symptoms, causes and treatment options.